The role of haustoria in sugar supply during infection of broad bean by the rust fungus Uromyces fabae - Voegele, Ralf T. (The National Academy of Sciences, 2001)
Biotrophic plant pathogenic fungi differentiate specialized infection structures within the living cells of their host plants. These haustoria have been linked to nutrient uptake ever since their discovery. We have for the first time to our knowledge shown that the flow of sugars from the host Vicia faba to the rust fungus Uromyces fabae seems to occur largely through the haustorial complex. One of the most abundantly expressed genes in rust haustoria, the expression of which is negligible in other fungal structures, codes for a hexose transporter. Functional expression of the gene termed HXT1 in Saccharomyces cerevisiae and Xenopus laevis oocytes assigned a substrate specificity for d-glucose and d-fructose and indicated a proton symport mechanism. Abs against HXT1p exclusively labeled haustoria in immunofluorescence microscopy and the haustorial plasma membrane in electron microscopy. These results suggest that the fungus concentrates this transporter in haustoria to take advantage of a specialized compartment of the haustorial complex. The extrahaustorial matrix, delimited by the plasma membranes of both host and parasite, constitutes a newly formed apoplastic compartment with qualities distinct from those of the bulk apoplast. This organization might facilitate the competition of the parasite with natural sink organs of the host.